The bahuvrīhi Compound Between Zeroing and Contrastive Accentuation: Vedic Sanskrit Model and Pāṇini’s Model - Paola Maria Rossi (Università degli Studi di Milano, 2021)
This article aims to explore how Pāṇini’s model of the bahuvrīhi compound may be diachronically correlated to the bahuvrīhi compound as attested in the Vedic Sanskrit language, thus accounting for the two Pāṇinian requisites: zero-ending for all the constituents and accentuation on the first constituent, contrastively employed in relation to the determinative compounds. Since Pāṇini’s work is based on the Brahmanical scholarly tradition, the sources of his bahuvrīhi model are also to be found in the Brahmanical scholarly milieux. The locus classicus is the case of índraśatru, which starts off the process of uniformation and regulation of bahuvrīhi compound stressed on the first constituent. The same scholarly-discussed índraśatru compound is mentioned in the late Rigvedic textual layer (R̥V 1.32.6; 1.32.10), as an expressive poetic device. Therefore, the two Pāṇinian characteristic traits of the bahuvrīhi compound are inherited from a peculiar blend of poetic language and linguistic exegesis.